An Instructional Model for Physical Education in the Next Era for Secondary School - Zhu , Jinyuan; Tongdecharoen, Wisute (International Journal of Sociologies and Anthropologies Science Reviews, 2023)
Background and Aim: Over the past three years of the COVID-19 pandemic, both the external sports environment for youth physical exercise and the national education policy landscape have undergone significant changes. In light of these developments and to align with physical education instruction in the next era, ensuring high-quality physical education, and promoting the physical fitness of young individuals, this study aims to construct a physical education instructional model “CISSO” (collaborate, input, school, student, output) to better regulate and optimize the process of physical education learning management and improving the quality of learning management. Methods: This study was future research conducted with phase 1 exploring the problem by reviewing literature and 5 experts through Semi-structured interviews, the PESTEL model, and the SIPOC model to analyze influencing factors, to drat physical education instructional concept model; phase 2 by questionnaires and modified Delphi to construct physical education instructional model “CISSO”; phase 3 connoisseurship to determine and evaluate the rationality of the CISSO model. Results: The CISSO Model contains factors of Collaborate, Input, School, Student, and Output such as: (1) Collaborate: a collaborative educational approach guided by the government, led by schools, and supported by social organizations and families. (2) Input: The key to governing school physical education management is to take more measures to increase comprehensive "Input" in school physical education learning. (3) School: The CISSO model places a significant emphasis on aligning with the Curriculum Standards (2022 Edition), and revolves around key components such as "learning, practicing, competing, and evaluation," resulting in a new and cohesive state of physical education. (4) Student: accentuates the subjectivity of students, with a pronounced focus on fostering their psychological development through sports education, thereby progressively instilling positive exercise routines. (5) Output: It holds the promise of driving improvements in students' physical abilities and fostering a greater sense of contentment among parents with the school's physical education initiatives. Conclusion: By implementing the CISSO model, educators and policymakers can gain a deeper understanding of the intricacies involved in managing physical education during the next era of education. The findings from this study will aid in making informed and wise decisions, enabling the formulation of effective strategies to optimize the learning experience of students in this dynamic educational landscape.